Leadership, discourse, and ethnicity - Holmes, Janet, 1947-; Marra, Meredith, 1974-; Vine, Bernadette (New York : Oxford University Press, 2011)
This is the first book in the field of workplace discourse to examine the relationships among leadership, ethnicity, and language use.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Communication in management; Diversity in the workplace; Leadership; Sociolinguistics